A Gestão do conhecimento no processo de expansão de cursos pré-vestibulares : estudo de caso do curso Fleming Medicina - Santos, Betover Godinho dos (Universidade do Vale do Rio dos Sinos, 2019)
This study discusses the construction of a pedagogical matrix, based on the Knowledge Management (KM) processes, with the perspective of market expansion in a pre-university preparation course focused on aprroval at medical schools. The chosen theme finds a significant lack of attention, both in the field of education and administration. As methodology, we opted for a qualitative study, using as research strategy a single case study, conducted in a pre-university preparation course for medicine in the city of Porto Alegre, Rio Grande do Sul. The data were collected through document analysis and semi-structured interviews with the main managers and teachers of the organization. From the data analysis, the results were structured in two phases: (a) presentation of the organization's characteristics and challenges, exploring its challenges and perspectives; and (b) proposition of a pedagogical matrix, structured from the study. It was found that the institution needs to improve its knowledge creation, storage, sharing and application processes, especially considering its expansion process. The analysis of the data led to the conclusion that the organization lacks a guiding plan with basic premises for the implementation of the Fleming Medicina project in the new units and existing headquarters. Thus, a pedagogical matrix was proposed that would improve the pedagogical management and knowledge management, as a tool for the process of expansion of the organization.
Keywords: Gestão do Conhecimento; Gestão Educacional; Projeto Político-Pedagógico; Cursos Pré-Vestibular; Knowledge Management; Educational Management; Political-Pedagogical Project; Pre-university Courses; ACCNPQ::Ciências Humanas::Educação